Recent Advancements and Current Status of Hydrogen Fuel Cells: Materials, Systems, Applications, and Commercialization Prospects - Pramodkumar M. Bagade; Preeti P. Gaikwad; Abhideep Bagade (International Journal of Electro-Mechanics and Material Behaviour, 2025)
In the transportation, stationary electricity, and industrial sectors, hydrogen fuel cells have become a crucial clean-energy technology that can help achieve worldwide decarbonization. Significant progress has been made in catalyst design, membrane engineering, stack architecture, system optimization, and hydrogen generation pathways throughout the last ten years (2018–2025). Platinum group metal (PGM) loading has been significantly reduced, single-atom and transition-metal-nitrogen-carbon (M-N-C) catalysts for oxygen reduction have been developed (Wu et al., 2022), proton exchange membranes in membrane electrode assembly (MEA) have been improved for durability (Pan et al., 2021), and green hydrogen has been scaled using sophisticated electrolyzers (Zhang et al., 2024). Strong legislative support and global electrolyzer deployment have advanced commercial demonstrations in fuel-cell vehicles, stationary solid oxide fuel cell systems, and micro combined heat-and-power (IRENA, 2020) (Talukdar et al., 2024). However, there are still major challenges, including cost, long-term durability, the lack of necessary materials, infrastructure gaps, and the carbon intensity of upstream hydrogen generation (Kafle et al., 2025). This overview summarizes recent advancements in materials, cell designs, hydrogen supply, applications, techno-economic trends, and future research directions. The report identifies key commercial challenges, outlines research objectives, and offers a roadmap for accelerating fuel-cell commercialization in developing hydrogen economies.
Keywords: Durability; Electrolyzer; Hydrogen fuel cell; MEA; PEMFC; SOFC; catalyst; green hydrogen